Fuzzy Model Tahani as Decision Support System for Employee Promotion - Abdullah, Dahlan; Djanggih, Hardianto; Suendri, S; Cipta, Hendra; Nofriadi, N (International Journal of Engineering and Technology, 2018)
Human resources within organization is very important to support the progress and quality of companies in achieving goals. Increased position is a very important factor for employee career planning and also to rejuvenate a position of occupation to be occupied by someone who has appropriate criteria to occupy a proposed position based on objective assessment and appropriate criteria variables. For that required a system that can assist leaders in making decisions for promotion of positions in accordance with what is expected from the company, it is necessary to design a decision support system using fuzzy database model Tahani method to assist in promotion.Â Â